Knowledge and attitudes towards dietary patterns and lifestyle during COVID-19 pandemic in Bangladesh: an online based cross-sectional study - Ielias Uddin; Rokon, M. Alshahria; Sabiha Sultana; Anika Jahin; Mursalin; Ibrahim Khan; Setu, Shraboni Sultana; Mahnaz Rahman; M. Sahedul Hasan; Empa Yeasmin; Rini, Asraul Hasibin (International Journal Of Community Medicine And Public Health, 2023)
Background: COVID-19 outbreak being the only pandemic of 21st century, that affected globally, has left us with some realization that elucidate the advancement in science and medicine is not enough to live a healthy life for the generation of modern era, if lifestyle and habitual factors are not controlled or maintained in proper way. In this study we aimed to find out people’s knowledge and attitudes about dietary patterns and lifestyle during COVID-19. Methods: An online based questionnaire was designed to collect the data based on the age limit of 15 to 60+ years. The survey was focused on both the affected and exposed individuals (n=853). The data was collected under three main sections containing questions about nutritional knowledge, preventive measures adapted by the respondents, lifestyle practices and their concerns. Results: The outcome of the study reveals, significant association between gender of the study and their food consumption diversity (p=0.026<0.05), participants awareness about COVID-19 depends on their education level. Study also displayed the infection rate, acceptance of vaccination, change of food habit and weight gain tendency depends on the age of the individual, showing statistical significance. Conclusions: The outcome of the study acquaints that proper balance between knowledge and practice, is the most important attitude, which can build prevention against any new public health threat like COVID-19 outbreak.